The Artist and Religion in the Contemporary World - Jasper, David (Text Matters: A Journal of Literature, Theory and Culture, 2011)
Although we begin with the words of the poet Henry Vaughan, it is the visual artists above all who know and see the mystery of the Creation of all things in light, suffering for their art in its blinding, sacrificial illumination. In modern painting this is particularly true of van Gogh and J.M.W. Turner. But God speaks the Creation into being through an unheard word, and so, too, the greatest of musicians, as most tragically in the case of Beethoven, hear their sublime music only in a profound silence. The Church then needs to see and listen in order, in the words of Heidegger, to learn to "dwell poetically on earth" before God. To dwell thus lies at the heart of its life, liturgically and in its pastoral ministry, as illustrated in the poetry of the English priest and poet, David Scott. This can also be seen as a "letting go" before God and an allowing of a space in which there might be a "letting the unsayable be unsaid" and order found even over the abyss. This is what Vladimir Nabokov has called "the marvel of consciousness" which is truly a seeing in the darkness. The poet, artist and musician can bring us close to the brink of the mystery, and thus the artist is always close to the heart of the church's worship and its ministry of care where words meet silence, and light meets darkness. Such, indeed, is the true marvel of consciousness in the ultimate risk which is the final vocation of the poet and artist, as it was of Christ himself, and all his saints. The church must be ever attentive to the deeply Christocentric ministry of art and the creative power of word and image in the letting the unsayable be unsaid. With the artist we may perhaps stand on Pisgah Height with Moses with a new imaginative perception of the divine Creation. The essay concludes on a personal note, drawing upon the author's own experience in retreat in the desert, with a reminder of the thought of Thomas Merton, a solitary in the community of the Church.